Accurate detection of intracellular microRNAs using functional Mo2C quantum dots nanoprobe. Issue 71 (20th August 2019) - Dai, Wenhao; Lu, Huiting; Yang, Fan; Dong, Haifeng; Zhang, Xueji
Abstract : A functionalized Mo2 C quantum dots nanoprobe was developed for accurate detection of intracellular mature microRNAs. Abstract : A programmable molecular beacon (MB) with a good discrimination capability for mature and precursor microRNAs was loaded onto the surface of Mo2 C quantum dots (QDs) for accurate detection of intracellular mature microRNAs.